Food and feeding habit of Tor putitora of Mahakali River, Nepal - Mahasetha, Vinod Kumar (BIBECHANA, 2015)
T.putitora is a sight feeder and can be categorized as column feeder, which at some stage resorts to bottom feeding as well. Depending upon the availability of food, the fish consumes a wide spectrum of dietary items varying from microscopic organisms and macrophytes to large number of insects and even small fishes.The feeding activities of T. putitora appeared to be good during pre-spawning (pre-monsoon) and post-spawning season while poor during monsoon or spawning season, which is directly related to the availability of food and maturation of gonads. The estimation of GSI (Gastro-somatic Index) also supported this fact.BIBECHANA 13 (2016) 115-125